1997
DOI: 10.1007/s003300050238
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive stress testing of myocardial ischemia: comparison of GRE-MRI perfusion and wall motion analysis to 99 mTc-MIBI-SPECT, relation to coronary angiography

Abstract: In the evaluation of ischemic heart disease only MR imaging seems to have the potential to assess myocardial perfusion, function, and coronary morphology on a single instrument. The aim of this study was to assess the feasibility of a stress test with dipyridamole (0. 56 mg/kg) to analyze myocardial perfusion by Gd first-pass enhancement in ultrafast gradient-recalled-echo MRI (perf-MRI), and wall motion by cine gradient-recalled-echo MRI (Cine-MRI) in one imaging session. Twelve patients underwent complete re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Previous reports revealed that MRI perfusion images are as good as conventional nuclear perfusion images. [36][37][38][39] As a result, we speculate that our results are also closely correlated with conventional nuclear perfusion imagings. Lastly, we did not evaluate the effect of coronary revascularization on MRI perfusion images.…”
Section: Discussionsupporting
confidence: 61%
“…Previous reports revealed that MRI perfusion images are as good as conventional nuclear perfusion images. [36][37][38][39] As a result, we speculate that our results are also closely correlated with conventional nuclear perfusion imagings. Lastly, we did not evaluate the effect of coronary revascularization on MRI perfusion images.…”
Section: Discussionsupporting
confidence: 61%
“…Wall-motion and wall thickening abnormalities reveals regional myocardial dysfunction (3,4). In our study, 75% of the severely stenotic or occluded vessels territories segments demonstrate wall motion abnormality.…”
Section: Sensky Et Almentioning
confidence: 81%
“…Myocardial oxygen need directly associates with perfusion thus in the evaluation of ischemia, perfusion is more sensitive than wall motion (4,5). In severe coronary arteries' stenosis collateral development can be insufficient resulting in functional impairment of the myocardial metabolism on the poststenotic region (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations